Analysis of The Effect of education, Health Expenditures and Per Capita Income To Human Development Index In Central Sulawesi Province For The Period 2015-2019 - Yunus, Santi (Green Publisher Indonesia, 2023)
The Human Development Index (HDI) is part of the development goals, high HDI is not easy to achieve, it takes the seriousness of the government to allocate budgets in the education sector and health expenditures. Per capita income is also part of increasing HDI. Central Sulawesi's HDI continues to increase from 2015-2019, the distribution of the education, health, and per capita income sectors also continues to increase. The purpose of this study was to determine the effect of expenditure in the education, health, and per capita income sectors on HDI in Central Sulawesi. The analysis tool used with panel data regression, the results of the study showed: Education sector expenditure had a negative but insignificant effect on the HDI of Central Sulawesi for the 2015-2019 period, while health sector expenditure had a positive and significant effect on HDI and per capita income had a negative and insignificant effect on the HDI of Central Sulawesi for the 2015-2019 period